Optimalisasi Konservasi Air melalui Lubang Resapan Biopori di Desa Ngaresrejo Sidoarjo - Sebastianus Priambodo; Yayu Sriwahyuni Hamzah; Ikhwanuddin Ikhwanuddin (Jurnal Kabar Masyarakat, 2026)
The declining capacity of soil to absorb rainwater due to land-use changes has contributed to increased surface runoff, local flooding, and reduced groundwater recharge. At the same time, household organic waste management in Ngaresrejo Village has not been optimally implemented, leading to environmental concerns. This community service program aimed to optimize groundwater recharge through the implementation of Biopore Infiltration Holes (BIH) based on community empowerment. The program was conducted in Ngaresrejo Village, Sukodono District, Sidoarjo Regency, involving 30 members of the Family Welfare Empowerment (PKK) as community partners. The program adopted a Participatory Rural Appraisal (PRA) approach consisting of site observation, participatory planning, educational counseling, technical training, hands-on BIH installation, mentoring, and monitoring and evaluation. Program effectiveness was assessed using pre-tests, post-tests, field observations, and participant satisfaction questionnaires. The results indicated that the average participants' knowledge score increased from 52.5% in the pre-test to 92.0% in the post-test, representing an improvement of 39.5%. Furthermore, 90% of participants were able to independently construct and maintain Biopore Infiltration Holes. The program also encouraged behavioral changes in household organic waste segregation, the application of bioactivators, and the establishment of community environmental cadres as local leaders in groundwater conservation. Therefore, the implementation of Biopore Infiltration Holes through a community empowerment approach proved effective in enhancing groundwater conservation, improving household organic waste management, and promoting environmental sustainability in Ngaresrejo Village.